1996
DOI: 10.1093/clinchem/42.8.1176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgen suppression by gonadotropin-releasing hormone agonist and flutamide on lipid metabolism in men with prostate cancer: focus on lipoprotein(a)

Abstract: No clear relation between lipoprotein(a) [Lp(a)] and endogenous gonadal hormones has been demonstrated. In this study, we compared the effects on Lp(a) of pharmacological castration in 50 patients with prostate cancer who were undergoing therapy with a gonadotropin-releasing hormone agonist (goserelin), with effects on 58 age-matched controls. We also studied 16 untreated patients under baseline conditions and after 3 months of therapy with goserelin alone or combined with an antiandrogen (flutamide). Neither … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These findings are in contrast with well documented findings of HDL‐C decrease after exogenous androgen administration in both sexes 31–37 . Accordingly, androgen deprivation induced by surgical or chemical castration is associated with increased HDL‐C and apoprotein AI concentrations 38–41 . Androgen supplementation in older people, however, did not show any effects on HDL; rather, a decline of LDL‐C has been reported 9, 11–13 …”
Section: Discussionmentioning
confidence: 62%
“…These findings are in contrast with well documented findings of HDL‐C decrease after exogenous androgen administration in both sexes 31–37 . Accordingly, androgen deprivation induced by surgical or chemical castration is associated with increased HDL‐C and apoprotein AI concentrations 38–41 . Androgen supplementation in older people, however, did not show any effects on HDL; rather, a decline of LDL‐C has been reported 9, 11–13 …”
Section: Discussionmentioning
confidence: 62%
“…A previous meta-analysis evaluated the effects of ADT on body composition and indicated that 6 out of 8 studies that evaluated BMI changes reported a significant increase of approximately 2.15% in BMI [11]. In the remaining two studies, no significant BMI increase was observed in one study, and a mean decrease of 0.39% was observed in the other study [36,37]. In our Ophthalmic Res 2023;66:272-280 DOI: 10.1159/000527387 study, although an increase of 0.88% was noted in the mean BMI value, this increase was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Neither cross-sectional nor prospective studies showed any significant effects of such therapy on Lp(a). However, cluster analysis suggests that the Lp(a) responses to androgen suppression are related to baseline concentrations of Lp(a) [51]. In another study, suppression of endogenous testosterone by the administration of Cetrorelix, an antagonist of GnRH, significantly increased Lp(a) levels by 40±60% in men [52].…”
Section: Sex Hormonesmentioning
confidence: 97%